REACTION FRITTING OF NANO-STRUCTURAL COVERINGS OF POW DER MATERIALS - V. M. Kovalevski; A. V. Kovalevskaja; S. V. Grigoijev; I. V. Fomihina; A. E. Zhuk (Литьë и металлургия)
Thin-film covers of silicon and carbon are received using the method of magnetron spraying of composite cathodes, the conditions of silicon carbide formation on diamond crystals are established.